2018
DOI: 10.3389/fonc.2018.00537
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Profiling of Prognostic Alternative Splicing Signature in Colorectal Cancer

Abstract: Background: This study was to explore differential RNA splicing patterns and elucidate the function of the splice variants served as prognostic biomarkers in colorectal cancer (CRC).Methods: Genome-wide profiling of prognostic alternative splicing (AS) events using RNA-seq data from The Cancer Genome Atlas (TCGA) program was conducted to evaluate the roles of seven AS patterns in 330 colorectal cancer cohort. The prognostic predictors models were assessed by integrated Cox proportional hazards regression. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 36 publications
3
34
0
Order By: Relevance
“…The present AS related genome-wide analysis identi ed seven AS modes in GBM patients, and showed that one gene was generally associated with two AS events, which is consistent with data in other tumors [26,27]. ES events accounted for approximately 50% of all AS events, indicating that they may be the most important AS events contributing to the malignancy of GBM; however, further functional experiments are necessary to con rm these ndings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The present AS related genome-wide analysis identi ed seven AS modes in GBM patients, and showed that one gene was generally associated with two AS events, which is consistent with data in other tumors [26,27]. ES events accounted for approximately 50% of all AS events, indicating that they may be the most important AS events contributing to the malignancy of GBM; however, further functional experiments are necessary to con rm these ndings.…”
Section: Discussionsupporting
confidence: 88%
“…Considering stable traits and the applicability of risk signatures [26][27][28]31], we developed seven prognostic signatures based on the top three survival-related AS events. The results showed that all the AS-related signatures could signi cantly distinguish the survival status and serve as independent indicators of unfavorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that alternative splicing (AS) is an important mechanism of post-transcriptional regulation that enables a single gene to produce multiple proteins, and nearly all human protein-coding genes will undergo alternative splicing [8]. Growing evidence has revealed that abnormal splicing events are closely related to carcinogenic processes including angiogenesis, apoptosis, proliferation, metastasis, and therapeutic drug resistance [9]. Thus, many cancer investigators are aware of the significance of AS and believe that it can take a potential role in therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have established the importance of alternative and aberrant splicing in cancer prognosis (Bjørklund et al, 2017;Li et al, 2017;Marcelino Meliso et al, 2017;Robertson et al, 2018;Zhu et al, 2018;Zong et al, 2018) and have begun to explore its potential relevance in cancer immunotherapy (Kahles et al, 2018;Wood et al, 2019). In this study, we explore "novel" exon-exon junction use among cancers with respect to a broad collection of normal tissues and cells.…”
Section: Discussionmentioning
confidence: 97%